2014
DOI: 10.1038/ismej.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of prebiotic-treated mice reveals novel targets involved in host response during obesity

Abstract: The gut microbiota is involved in metabolic and immune disorders associated with obesity and type 2 diabetes. We previously demonstrated that prebiotic treatment may significantly improve host health by modulating bacterial species related to the improvement of gut endocrine, barrier and immune functions. An analysis of the gut metagenome is needed to determine which bacterial functions and taxa are responsible for beneficial microbiota–host interactions upon nutritional intervention. We subjected mice to preb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
422
6
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(483 citation statements)
references
References 54 publications
48
422
6
7
Order By: Relevance
“…These findings provide a proof of concept for the potential of in vivo selection to identify synbiotic combinations that are, in ecological terms, highly synergistic. In addition to enhancing the abundance of strain IVS-1, the synbiotic used here also redressed the high-fatdiet-induced reduction in the level of bifidobacteria detected in rats that is often reported in the literature (41)(42)(43). Therefore, although no metabolic benefits were seen in the rat model used in our study, the synbiotic may be beneficial in other scenarios, as bifidobacteria are considered health-promoting organisms (6,26,(66)(67)(68).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…These findings provide a proof of concept for the potential of in vivo selection to identify synbiotic combinations that are, in ecological terms, highly synergistic. In addition to enhancing the abundance of strain IVS-1, the synbiotic used here also redressed the high-fatdiet-induced reduction in the level of bifidobacteria detected in rats that is often reported in the literature (41)(42)(43). Therefore, although no metabolic benefits were seen in the rat model used in our study, the synbiotic may be beneficial in other scenarios, as bifidobacteria are considered health-promoting organisms (6,26,(66)(67)(68).…”
Section: Discussioncontrasting
confidence: 40%
“…2A). Decreases in numbers of bifidobacteria are often observed during high-fat-diet feeding (41)(42)(43). To determine if our synbiotic strategy could redress this decrease, we employed a rat model of highfat-diet-induced NAFLD where rats develop steatosis (fatty liver) but do not show an increase in body weight, develop liver inflammation, or progress to nonalcoholic steatohepatitis (NASH) (28).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice have shown that oligofructose (a fruc tan) reduced diet induced obesity, diabetes, hepatic steato sis and inflammation by mechanisms linked with changes in specific gut microorganisms and meta genomics functions of bacteria 72 . A study in rats suggested that oligo fructose consumption might normalize the metabolomic signature of insulin resistance in obese rats and reduce obesity in offspring 73 .…”
Section: Prebiotic Utilization and Host Healthmentioning
confidence: 99%
“…For instance, a 5 d animal-based-diet significantly altered the abundance of twenty-two clusters, elevated faecal bile acid concentration, and increased BSH expression (99) . Everard et al (100) describe that high-fat feeding significantly affected twenty genera. This may have been influenced by a decline in the antimicrobial peptide regenerating islet-derived protein three gamma.…”
Section: Dietary Interventionmentioning
confidence: 99%